The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1016/j.jneb.2020.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Food Skills and Their Relationship with Food Security and Dietary Diversity Among Asylum Seekers Living in Norway

Abstract: Objective: To investigate the impact of food skills on food security and dietary diversity among asylum seekers living in Norwegian reception centers. Design: Cross-sectional study. Setting: Eight asylum reception centers. Participants: A total of 205 asylum seekers (131 men and 74 women) recruited through convenience sampling. Main Outcome Measures: Food skills were measured using questions from the Canadian Rapid Response on Food Skills and divided into cooking skills and shopping skills. Food security was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
3
0
2
Order By: Relevance
“…For example, older people tend to have less dietary diversity than the younger population because they rely on their familiar experiences and their dietary restrictions according to their health status [17]. Further, cooking skills have been suggested as a determinant for dietary diversity, and the male elderly who tend to have lower cooking skills are shown to have lower DD than the female elderly [18]. Policies can also influence DD.…”
Section: Introductionmentioning
confidence: 99%
“…For example, older people tend to have less dietary diversity than the younger population because they rely on their familiar experiences and their dietary restrictions according to their health status [17]. Further, cooking skills have been suggested as a determinant for dietary diversity, and the male elderly who tend to have lower cooking skills are shown to have lower DD than the female elderly [18]. Policies can also influence DD.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural teaching approaches employed in secondary schools have been shown to positively contribute to skills development leading to increased food security [ 50 ]. In contrast, another study showed that food skills had a limited association with food security and dietary diversity [ 51 ]. According to our results, the next strongest correlation was related to physical domain.…”
Section: Discussionmentioning
confidence: 99%
“…Per raccogliere i dati della nostra indagine sono stati utilizzatii metodi sia quantitativi sia qualitativi. Parte dei risultati di questi studi è stata pubblicata in altri articoli (Terragni et al, 2018;Barbala et al, 2019;Henjum, Casweel e Terragni, 2019;Terragni, Arnold e Henjum, 2020). I dati sono qui presentati in forma nuova, dando una visione d'insieme del fenomeno con un maggiore accento sui dati quantitativi.…”
Section: Metodologiaunclassified
“…Le donne, invece, sembrano in grado, in una certa misura, di (ri)utilizzare il proprio "capitale culturale culinario" preparando dei pasti più variati anche in condizioni di ristrettezze economiche. Questo tema è stato approfondito in un altro articolo basato sui dati di questa ricerca (Terragni, Arnold, Henjum, 2020) e trova conferme anche in altri studi (Nielsen et al, 2015;Pfeiffer, Ritter e Oestreicher 2015). Ciò nonostante anche per donne, specie quelle con figli, emerge la fatica di mettere sul tavolo colazione pranzo e cena ogni giorno.…”
Section: Cucinare I Pastiunclassified